Preparation method for synthesizing high-purity quartz sand from natural quartz

Through the methods of airflow grinding, ion exchange and sol-gel purification, the problems of insufficient purity of high-purity quartz sand and high waste liquid treatment cost in the prior art are solved, and the preparation and cost of high-purity quartz sand are achieved.

CN119390345APending Publication Date: 2025-02-07JIANGSU XINHUA SEMICON TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411521767.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to prepare high-purity quartz sand that meets the requirements of electronic-grade silicon field in the prior art, and the traditional purification process generates a large amount of waste liquid, which increases costs.

Method used

The natural quartz sand is grinded to the submicron level by airflow milling, which enhances chemical reactivity, and is further purified by ion exchange and sol-gel method, and finally crystallization is made by calcination.

Benefits of technology

The purity of quartz sand is significantly improved to reach ≥99.999%, meeting the needs of electronic grade silicon materials, and reducing the cost of waste liquid treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390345A_ABST
    Figure CN119390345A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-purity quartz sand, in particular to a preparation method for synthesizing high-purity quartz sand from natural quartz, which mainly comprises the following steps: selecting proper quartz sand, and grinding to submicron by using a jet mill; adding an alkaline solution into the sample, fully stirring, filtering, and preparing silicon dioxide sol through ion exchange; standing and aging to obtain silicon dioxide gel; and finally, drying, grinding and calcining to obtain the high-purity quartz sand. The particle size of the quartz sand is controlled at the submicron level, the apparent activation energy of the quartz sand is reduced, formation of-Si-O-Si-in the hydrolytic condensation process is facilitated, meanwhile, chemical purification treatment is carried out after jet milling, subsequent impurity removal is more thorough, then calcination is carried out after gelling, the crystal structure is more uniform and pure, and the preparation method is suitable for industrial production. The purity of calcined silicon dioxide and the crystal quality are remarkably improved, the purity of high-purity quartz can be larger than or equal to 99.999%, and the high-purity quartz can be used for preparing a quartz crucible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-purity quartz sand materials, and in particular to a method for preparing high-purity quartz sand synthesized from natural quartz. Background Art

[0002] High-purity quartz sand (SiO2 ≥ 99.9%) has excellent physical and chemical properties, such as high heat resistance (melting point is about 1723 ° C), strong corrosion resistance, low thermal expansion, good insulation, strong hardness, etc. It is an industrial raw material needed by high-tech industries. In addition, high-purity quartz sand has excellent ductility and is easy to process into products of various shapes. At the same time, it has excellent stability and electrical properties in high temperature and high pressure environments. Therefore, high-purity quartz sand is widely used in semiconductors, photovoltaics, optical fibers and aerospace fields. In the semiconductor field, quartz crucible is one of the key auxiliary materials for the preparation of single crystal silicon, and high-purity quartz sand is an important raw material for the inner layer of the quartz crucible. Its purity directly affects the quality and quality of single crystal pulling.

[0003] With the development of high-tech industries, the requirements for quartz purity are also constantly increasing. At present, high-purity quartz sand is mainly obtained from natural quartz ore through crushing, grinding, impurity removal and other purification processes. However, the raw ore of high-purity quartz sand mainly comes from abroad. my country's quartz ore mainly comes from Lingqiu Mountain hot vein quartz, in which the SiO2 content is about 99.35%, which has the ability to prepare high-purity quartz sand. The purity of quartz sand prepared by traditional purification methods is limited, and it is difficult to meet the requirements of quartz crucible purity in the field of electronic-grade silicon (>99.999%), and the cost of synthesizing high-purity quartz sand with pure chemical reagents is expensive. The cost problem is the main reason for its difficulty in large-scale production.

[0004] The traditional method of purifying natural quartz includes calcination, quenching, drying, grinding, flotation, acid leaching and other steps. First, the natural quartz ore after beneficiation is washed with water, acid and alkali in turn to remove impurities in the ore; secondly, the ore after impurity removal is calcined and water quenched; then the natural quartz ore is crushed and pulverized by a jaw crusher and a roller mill; then the quartz sand is screened, washed and dried; finally, high-purity quartz sand is obtained after acid leaching, washing and drying. The purity of the quartz sand purified by the above method is about 4N, which does not meet the requirements of the electronic grade silicon field.

[0005] In addition, the early treatment process of natural quartz also has an important impact on the subsequent synthetic quartz. Chinese patent CN117483092A discloses a natural quartz purification process, which mainly includes the following steps: first, the quartz sample is screened and magnetically separated; secondly, the slurry pH is adjusted to acidic with HF, and reverse flotation is performed with a collector; then the pH is adjusted to alkaline, and the impurity minerals are removed by adding a collector, an activator, and a synergist, and then the impurity minerals are washed with deionized water and dried; then the impurity minerals are washed with deionized water after calcination in a muffle furnace, and finally the water-quenched sample is heated and stirred with a mixed acid, filtered, washed, and dried to obtain a high-purity quartz sand product. Chinese patent CN 109019609 A discloses a method for preparing high-purity quartz from natural powder quartz, which mainly includes the following steps: first, natural powder quartz is mixed with ammonium sulfate and calcined at 500-550°C for 2-3h, the calcined product is washed with deionized water, and then placed in a mixed solution of sulfuric acid and hydrofluoric acid for acid leaching, and then washed and dried again to obtain a high-purity powder quartz product. The above methods all obtain high-purity quartz products by purifying natural quartz, but the purity of the obtained quartz products does not meet the purity requirements of electronic-grade silicon for quartz crucibles. At the same time, a large amount of waste liquid is generated during the purification process, which increases the cost of waste liquid treatment.

[0006] Chinese patent CN 115744920 A discloses a method for synthesizing high-purity quartz by hydrothermal method, which mainly includes the following steps: first, 82-85% of mineralizer is loaded into the autoclave; then, the quartz raw material is washed with water, washed with alkali, and then dried after washing and placed in the dissolution zone of the autoclave, and the quartz seed crystal is acid-leached and vertically hung on the crystal growth rack in the autoclave, and the two zones are separated and sealed by a throttling baffle; then, the pressure in the autoclave is controlled to be 120-140MPa, the temperature in the crystallization zone is 310-550℃, and the temperature in the dissolution zone is 360-370℃, so that the high-purity quartz grows naturally; finally, the grown quartz is crushed, acid-leached, and washed to obtain high-purity quartz. This method prepares high-purity quartz sand by natural growth of seed crystals, and 100-140kg of quartz sand can be obtained in one growth. However, the average growth period of quartz is 15-30 days, and its growth period is long, and the energy consumption is high, which is not suitable for large-scale production.

[0007] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing high-purity quartz sand synthesized from natural quartz, which uses a jet mill to grind natural quartz sand to a submicron level, thereby enhancing the chemical reactivity of the quartz sand and improving the efficiency and purity of the synthetic quartz for preparing semiconductor-grade quartz crucible quartz sand or quartz glass.

[0009] The above technical objectives of the present invention are achieved through the following technical solutions:

[0010] A method for preparing high-purity quartz sand by synthesizing natural quartz sand comprises the following steps:

[0011] Step 1, select natural quartz sand with SiO2 content greater than 99% as raw material, use a sieve to control its particle size to less than 200 μm, and wash and dry after screening;

[0012] Furthermore, in step 1, the cleaning includes: first, using deionized water with a pH of 6.8 to 7.2 to wash away dust impurities on the surface of the quartz sand, then using a 0.1 mol / L hydrochloric acid solution for pickling, then using deionized water for water washing again, and finally using a vacuum drying oven for drying, with the pressure set to -0.1 MPa, the temperature set to 40 to 60°C, and the drying time being 4 to 8 hours. The control of the pH value ensures that the structure of the quartz sand is not destroyed. Pickling can remove metal ions and other acid-soluble impurities, and promote the purification effect of subsequent reactions.

[0013] Step 2, grinding the quartz sand with a jet mill and then sieving; wherein the mesh size of the sieve is 125000 to 12500 mesh, i.e. 0.2-1 μm, and the grinding time is 1 to 6 hours;

[0014] Further, in step 2, the airflow mill uses a jet-type airflow mill with a working pressure of 0.3-0.8 MPa and a feed rate of 2-8 kg / h; the speed of the classifying wheel is 1500-3200 r / min; the frequency of the feeder is 25-45 Hz; the frequency of the induced draft fan is 30-45 Hz, and the gas flow rate is 200-300 m / s; argon, nitrogen or helium is used as the material carrier gas. In the process of crushing natural quartz stone, jaw crushers and roller mills are commonly used to crush and grind natural quartz stone, and the obtained quartz sand particle size is 1-300 μm. On this basis, the quartz sand particle size can be ground to a submicron level of 0.1-1 μm by using an airflow mill. The smaller the quartz sand particle size, the larger the specific surface area, and the chemical reaction rate and reaction order increase; the submicron particle size increases the specific surface area and enhances the chemical reactivity. The role of the airflow mill can achieve the homogenization of the material while reducing the heat effect. At the same time, submicron quartz sand contains more Si-OH bonds, which can generate intermediate products with lower polymerization degree, greatly improving the efficiency of hydrolysis synthesis of high-purity quartz.

[0015] Furthermore, in step 2, the quartz sand particle size is divided into larger than 1 μm, 1-0.5 μm, 0.5-0.2 μm, and smaller than 0.2 μm through a sieve.

[0016] Step 3, putting the screened quartz sand into a reactor, and adding alkaline solution to fully stir the reaction;

[0017] Further, in step 3, the alkaline solution includes one of sodium hydroxide and potassium hydroxide or a mixture thereof, the concentration is 1.2 to 4.5 mol / L, the reaction temperature is 60 to 220° C., the reaction time is 4 to 10 hours, and the alkaline solution reacts with the miscellaneous elements in the quartz sand to form a silicon slag precipitate, such as Al, Fe and other elements to form a low-solubility compound precipitate.

[0018] Step 4, filtering the solution in step 3 to remove precipitated impurities, and removing alkali metal ions through a strong acid cation exchange column, specifically exchanging metal ions with hydrogen ions on the resin, wherein the solution flow rate is 60 to 180 L / min;

[0019] Wherein, in step 4, the strong acid cation exchange resin is 732 type, and in order to prevent the sol from forming a gel after ion exchange, the temperature is controlled at 8-15° C. and the pH is 2-3.

[0020] Step 5, placing the sol obtained in step 4 into a reaction kettle, starting stirring, standing for aging after stirring, washing with deionized water for multiple times after aging, and drying after washing;

[0021] Further, in step 5, the stirring temperature is 40-120°C, the stirring speed is 80-350r / min, and the stirring time is 2-15h; the standing temperature is 60-100°C, and the standing time is 0.5-3h; the aging temperature is 70-140°C, and the aging time is 3-18h; the drying temperature is 120-260°C, and the drying time is 18-36h; all are carried out under the protection of an inert atmosphere. The inert protective gas is nitrogen, helium or argon, the gas purity is ≥99.99%, and the gas flow rate is 200-500mL / min. The sol is continuously hydrolyzed and condensed to form silicon oxygen bonds, and gradually converted into a wet silica gel, and the moisture in the wet gel is removed by drying to further form a silica dry gel.

[0022] Furthermore, in step 5, the inner surface of the reactor is a phenolic coating or a high temperature and corrosion resistant coating with a thickness greater than 15 μm.

[0023] Step 6, using a crusher to crush the dried gel, using a screen to control the quartz sand particle size range to 100-600 μm, and then placing the quartz sand in a high-temperature furnace for calcination and crystallization, the calcination temperature is 1000-1300°C, and the calcination time is 12-36 hours. During the drying process, the water in the sol evaporates, making the structure of the silicon dioxide dense. The calcination process promotes the formation of the crystal structure and removes the remaining impurities through high temperature to form stable silicon dioxide crystals.

[0024] Furthermore, in step 6, the crusher is a double-toothed roller crusher, the roller shaft is made of high-purity quartz with a purity of ≥99.99%, and the rotation speed is 10 to 120 r / min; the high-temperature furnace is a microwave rotary furnace with a power of 120 to 200 kW and a rotation speed of 0.5 to 2 r / min.

[0025] In summary, the present invention has the following beneficial effects:

[0026] In the traditional natural quartz sand purification process, calcination usually occurs after crushing, and impurities are often enclosed in the crystal during the calcination process, which is difficult to further remove, resulting in the purity being difficult to meet the requirements of the electronic grade silicon field. The present invention controls the quartz sand particle size to the submicron level through airflow milling, reduces the apparent activation energy of the quartz sand, obtains intermediate products with a low degree of polymerization, is conducive to the formation of -Si-O-Si- during the hydrolysis and condensation process, and further improves the efficiency. At the same time, chemical purification treatment is carried out after airflow milling, so that the subsequent impurity removal is more thorough, and then calcined after gel formation, the crystal structure is more uniform and pure, so that the purity of silicon dioxide and the quality of the crystal after calcination are significantly improved, and the purity of high-purity quartz can be made ≥99.999%, which can be used to prepare quartz crucibles.

[0027] The present invention is directed to natural quartz sand, and during the process of introducing ion exchange and sol-gel method, the removal efficiency of impurities is significantly improved, so that it can produce quartz sand with higher purity, which is particularly suitable for applications requiring ultra-high purity, such as electronic-grade silicon materials. The quartz sand particles after fine crushing have a smaller particle size and a larger surface area, and can be fully contacted with chemical reagents, thereby greatly improving the reaction rate and the efficiency of ion exchange. Based on the characteristics of the particles after fine crushing, the present invention makes the chemical purification effect more thorough than the traditional process, ensuring that most of the impurities have been removed before calcination.

[0028] Whether it is natural quartz sand purification or synthetic quartz sand, traditional processes have their own limitations. The natural quartz sand purification process usually focuses on physical and chemical purification, while the synthetic quartz sand process is mostly a complex high-temperature synthesis process. The present invention breaks the boundary between the two and achieves new effects by introducing new steps. It is a brand-new technical path. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments in the records of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is an optical microscope image of high-purity synthetic quartz in Example 1 of the present invention.

[0031] Figure 2 The present invention is a flowchart of the steps of synthesizing high-purity quartz sand from natural quartz stone in an embodiment of the present invention.

[0032] Figure 3 1 is a comparison chart of the total impurity content of high-purity quartz in the embodiments of the present invention. DETAILED DESCRIPTION

[0033] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the technical scheme proposed according to the present invention, its specific implementation method, characteristics and effects are described in detail as follows.

[0034] Sources of raw materials used in the embodiments and comparative examples:

[0035] Components Commercial sources Quartz sand Maolin Quartz Sand Trading Co., Ltd. Potassium hydroxide Sinopharm Chemical Reagent Co., Ltd. Sodium hydroxide Sinopharm Chemical Reagent Co., Ltd. Strong acid cation exchange column Suzhou Bojie Resin Technology Co., Ltd.

[0036] Example 1

[0037] like Figure 1 to Figure 3 As shown, this embodiment uses natural quartz sand with a particle size of 1 to 0.5 μm as a raw material to prepare high-purity quartz sand.

[0038] Step 1: First, use a screen to control the particle size of quartz sand to less than 200 μm, then use deionized water to clean the dust and other impurities on the surface of the quartz sand, then use hydrochloric acid solution to pickle the quartz sand and then use deionized water to wash it, and finally use a vacuum drying oven to dry for 4 hours. The vacuum drying oven pressure is set to -0.1 MPa and the temperature is set to 40°C.

[0039] Step 2: Grind the quartz sand using a jet mill for 1 h, and control the particle size of the quartz sand to 1-0.5 μm through a sieve.

[0040] Step 3, take quartz sand with a particle size of 1 to 0.5 μm and put it into a reactor, and add a sodium hydroxide solution with a concentration of 4 mol / L, with a solid-liquid ratio of 1:8, and stir the reaction at 120° C. for 4 h.

[0041] Step 4, filtering the solution in step 3 through a filter with an accuracy of 0.2 μm to precipitate impurities, and then removing alkali metal ions through an ion exchange column, with a solution flow rate of 120 L / min.

[0042] Step 5, placing the sol in a reactor, stirring for 4 h under the protection of nitrogen, with a stirring rate of 180 r / min and a stirring temperature maintained at 65°C; after stirring, keeping the temperature at 65°C for 0.5 h; after the sol is converted into gel, adjusting the temperature of the reactor to 100°C, and aging for 10 h under the protection of nitrogen; after aging, soaking in deionized water for 1 h, draining the waste water and then washing it 3 times; the washed gel is dried under the protection of nitrogen, the drying temperature is 215°C, and the drying time is 18 h.

[0043] Step 6, using a double-toothed roller crusher to crush the dried gel, adjusting the roller gap to 0.2 mm, and using a screen to control the gel particle size to 100-300 μm; transferring the screened gel to a high-temperature furnace for calcination, maintaining the temperature at 1250° C. for 20 hours.

[0044] Among them, the detection components of high-purity quartz sand are shown in Table 1:

[0045] Table 1 Example 1 High purity quartz composition (unit: ppm)

[0046] element Al B Fe Cu Cr K Mn Zn Na Ti P Ni Mg total SQ1 0.28 0.06 0.20 0.03 0.02 0.03 0.02 0.04 0.16 0.03 0.02 0.02 0.02 0.93

[0047] Example 2

[0048] In this embodiment, natural quartz sand with a particle size of 0.5 to 0.2 μm is used as a raw material to prepare high-purity quartz sand.

[0049] Step 1: First, use a screen to control the particle size of quartz sand to less than 200 μm, then use deionized water to clean the dust and other impurities on the surface of the quartz sand, then use hydrochloric acid solution to pickle the quartz sand and then use deionized water to clean it, and finally use a vacuum drying oven to dry it for 4 hours. The vacuum drying oven pressure is set to -0.1 MPa and the temperature is set to 42°C.

[0050] Step 2: Grind the quartz sand using a jet mill for 1.5 hours, and control the particle size of the quartz sand to 0.5-0.2 μm through a sieve.

[0051] Step 3, take quartz sand with a particle size of 0.5-0.2 μm and put it into a reactor, and add a potassium hydroxide solution with a concentration of 4 mol / L, with a solid-liquid ratio of 1:9, and stir the reaction at 130° C. for 4.5 hours.

[0052] Step 4, filtering the solution in step 3 through a filter with an accuracy of 0.2 μm to precipitate impurities, and then removing alkali metal ions through an ion exchange column, with a solution flow rate of 128 L / min.

[0053] Step 5, putting the sol into a reactor, stirring for 4 hours under the protection of nitrogen, the stirring rate is 190r / min, and the stirring temperature is maintained at 60°C; after stirring, the temperature is kept at 60°C for 0.5 hours; after the sol is converted into gel, the temperature of the reactor is adjusted to 120°C, and aged for 12 hours under the protection of nitrogen; after aging, it is soaked in deionized water for 1 hour, and the waste water is discharged and then washed three times; the washed gel is dried under the protection of nitrogen, the drying temperature is 220°C, and the drying time is 20 hours.

[0054] Step 6, using a double-toothed roller crusher to crush the dried gel, adjusting the roller gap to 0.25 mm, and using a screen to control the gel particle size to 100-300 μm; transferring the screened gel to a high-temperature furnace for calcination, maintaining the temperature at 1250° C. for 18 hours.

[0055] Among them, the detection components of high-purity quartz sand are shown in Table 2:

[0056] Table 2 Example 2 High purity quartz composition (unit: ppm)

[0057] element Al B Fe Cu Cr K Mn Zn Na Ti P Ni Mg total SQ1 0.24 0.02 0.21 0.02 0.03 0.12 0.01 0.02 0.09 0.03 0.01 0.01 0.01 0.82

[0058] Example 3

[0059] In this embodiment, natural quartz sand with a particle size less than 0.2 μm is used as a raw material to prepare high-purity quartz sand.

[0060] Step 1: First, use a screen to control the particle size of quartz sand to less than 200 μm, then use deionized water to clean the dust and other impurities on the surface of the quartz sand, then use hydrochloric acid solution to pickle the quartz sand and then use deionized water to clean it, and finally use a vacuum drying oven to dry it for 4 hours. The vacuum drying oven pressure is set to -0.1 MPa and the temperature is set to 45°C.

[0061] Step 2: Grind the quartz sand using a jet mill for 2 hours, and control the particle size of the quartz sand to less than 0.2 μm through a sieve.

[0062] Step 3, take quartz sand with a particle size of less than 0.2 μm and put it into a reactor, and add a potassium hydroxide solution with a concentration of 4 mol / L, with a solid-liquid ratio of 1:9, and stir the reaction at 125° C. for 5 hours.

[0063] Step 4, filtering the solution in step 3 through a filter with an accuracy of 0.2 μm to precipitate impurities, and then removing alkali metal ions through an ion exchange column, with a solution flow rate of 132 L / min.

[0064] Step 5, putting the sol into a reactor, stirring for 3 hours under the protection of nitrogen, the stirring rate is 170r / min, and the stirring temperature is maintained at 70°C; after stirring, the temperature is kept at 70°C for 1 hour; after the sol is converted into gel, it is transferred to a reactor, the temperature of the reactor is adjusted to 110°C, and it is aged for 9 hours under the protection of nitrogen; after the aging is completed, it is soaked in deionized water for 1 hour, and the waste water is discharged and then washed twice; the washed gel is dried under the protection of nitrogen, the drying temperature is 205°C, and the drying time is 24 hours.

[0065] Step 6, using a double-toothed roller crusher to crush the dried gel, adjusting the roller gap to 0.25 mm, and using a screen to control the gel particle size to 100-300 μm; transferring the screened gel to a high-temperature furnace for calcination, maintaining the temperature at 1250° C. for 22 hours.

[0066] Among them, the detection components of high-purity quartz sand are shown in Table 3:

[0067] Table 3 Example 3 High purity quartz composition (unit: ppm)

[0068] element Al B Fe Cu Cr K Mn Zn Na Ti P Ni Mg total SQ1 0.21 0.03 0.18 0.02 0.02 0.08 0.01 0.01 0.02 0.01 0.02 0.01 0.01 0.63

[0069] In order to better reflect the advantages of the present invention, high-purity quartz sand was prepared by using natural quartz sand without airflow milling as a comparative example, and the particle size of the natural quartz sand was controlled to be greater than 200 μm, 200-80 μm, and 80-1 μm by using a sieve.

[0070] Comparative Example 1

[0071] In this comparative example, natural quartz sand with a particle size of 80 to 1 μm is used as a raw material to prepare high-purity quartz sand, and the natural quartz sand used is not finely ground by air flow.

[0072] Step 1: First, use deionized water to clean the dust and other impurities on the surface of the quartz sand, dry it in a vacuum oven for 3 hours, and then sieve the quartz sand with a screen to control the particle size of the quartz sand to 80-1 μm. The vacuum oven pressure is set to -0.1 MPa and the temperature is set to 40°C.

[0073] Step 2, take quartz sand with a particle size of 80 to 1 μm and put it into a reactor, and add a sodium hydroxide solution with a concentration of 4 mol / L, with a solid-liquid ratio of 1:8, and stir the reaction at 130° C. for 4 hours.

[0074] Step 3, filtering the solution in step 2 through a filter with an accuracy of 0.2 μm to precipitate impurities, and then removing alkali metal ions through an ion exchange column, with a solution flow rate of 138 L / min.

[0075] Step 4, placing the sol in a reactor, stirring for 2.5 hours under the protection of nitrogen, the stirring rate is 175r / min, and the stirring temperature is maintained at 68°C; after stirring, the temperature is maintained at 68°C for 1.5 hours; after the sol is converted into gel, it is transferred to a reactor, the temperature of the reactor is adjusted to 100°C, and it is aged for 10 hours under the protection of nitrogen; after the aging is completed, it is soaked in deionized water for 1 hour, and the waste water is discharged and then washed three times; the washed gel is dried under the protection of nitrogen, the drying temperature is 220°C, and the drying time is 16 hours.

[0076] Step 5, crushing the dried gel with a double-toothed roller crusher, adjusting the roller gap to 0.25 mm, and controlling the gel particle size to 100-300 μm with a screen; transferring the screened gel into a high-temperature furnace for calcination, maintaining the temperature at 1250° C. for 22 hours.

[0077] Among them, the detection components of high-purity quartz sand are shown in Table 4:

[0078] Table 4 Comparative Example 1 High Purity Quartz Composition (Unit: ppm)

[0079] element Al B Fe Cu Cr K Mn Zn Na Ti P Ni Mg total SQ1 0.46 0.04 0.27 0.04 0.03 0.03 0.01 0.08 0.19 0.02 0.03 0.01 0.01 1.22

[0080] Comparative Example 2

[0081] In this embodiment, natural quartz sand with a particle size of 200-80 μm is used as a raw material to prepare high-purity quartz sand, and the natural quartz sand used is not finely ground by air flow.

[0082] Step 1: First, use deionized water to clean the dust and other impurities on the surface of the quartz sand, dry it in a vacuum oven for 3.5 hours, and then sieve the quartz sand with a sieve to control the particle size of the quartz sand to 80-1 μm. The vacuum oven pressure is set to -0.1 MPa and the temperature is set to 40°C.

[0083] Step 2, take quartz sand with a particle size of 200 to 80 μm and put it into a reactor, and add a potassium hydroxide solution with a concentration of 4 mol / L, with a solid-liquid ratio of 1:8, and stir the reaction at 120° C. for 4 hours.

[0084] Step 3, filtering the solution in step 2 through a filter with an accuracy of 0.2 μm to precipitate impurities, and then removing alkali metal ions through an ion exchange column, with a solution flow rate of 134 L / min.

[0085] Step 4, putting the sol into a reactor, stirring for 2 hours under the protection of nitrogen, the stirring rate is 150r / min, and the stirring temperature is maintained at 60°C; after stirring, keeping the temperature at 60°C for 2 hours; after the sol is converted into gel, transfer it to a reactor, adjust the temperature of the reactor to 120°C, and age it for 12 hours under the protection of nitrogen; after the aging is completed, soak it in deionized water for 1 hour, drain the waste water and then wash it 3 times; the washed gel is dried under the protection of nitrogen, the drying temperature is 220°C, and the drying time is 18 hours.

[0086] Step 5, crushing the dried gel with a double-toothed roller crusher, adjusting the roller gap to 0.25 mm, and controlling the gel particle size to 100-300 μm with a screen; transferring the screened gel into a high-temperature furnace for calcination, maintaining the temperature at 1250° C. for 20 hours.

[0087] Among them, the detection components of high-purity quartz sand are shown in Table 5:

[0088] Table 5 Comparative Example 2 High Purity Quartz Composition (Unit: ppm)

[0089] element Al B Fe Cu Cr K Mn Zn Na Ti P Ni Mg total SQ1 0.58 0.06 0.37 0.08 0.04 0.22 0.02 0.06 0.07 0.03 0.02 0.02 0.04 1.61

[0090] Comparative Example 3

[0091] In this comparative example, natural quartz sand with a particle size greater than 200 μm is used as a raw material to prepare high-purity quartz sand, and the natural quartz sand used is not finely ground by air flow.

[0092] Step 1: First, use deionized water to clean the dust and other impurities on the surface of the quartz sand, dry it in a vacuum oven for 4 hours, and then sieve the quartz sand with a screen to control the quartz sand particle size to be greater than 200 μm. The vacuum oven pressure is set to -0.1 MPa and the temperature is set to 40°C.

[0093] Step 2, take quartz sand with a particle size greater than 200 μm and put it into a reactor, and add a sodium hydroxide solution with a concentration of 4 mol / L, with a solid-liquid ratio of 1:9, and stir the reaction at 126° C. for 4 hours.

[0094] Step 3, filtering the solution in step 2 through a filter with an accuracy of 0.2 μm to precipitate impurities, and then removing alkali metal ions through an ion exchange column, with a solution flow rate of 136 L / min.

[0095] Step 4, putting the sol into a reactor, stirring for 3 hours under the protection of nitrogen, the stirring rate is 195r / min, and the stirring temperature is maintained at 65°C; after stirring, the temperature is kept at 65°C for 2 hours; after the sol is converted into gel, it is transferred to a reactor, the temperature of the reactor is adjusted to 105°C, and it is aged for 10 hours under the protection of nitrogen; after the aging is completed, it is soaked in deionized water for 1 hour, and the waste water is discharged and then washed three times; the washed gel is dried under the protection of nitrogen, the drying temperature is 220°C, and the drying time is 14 hours.

[0096] Step 5, crushing the dried gel with a double-toothed roller crusher, adjusting the roller gap to 0.25 mm, and controlling the gel particle size to 100-300 μm with a screen; transferring the screened gel into a high-temperature furnace for calcination, maintaining the temperature at 1250° C. for 22 hours.

[0097] Among them, the detection components of high-purity quartz sand are shown in Table 6:

[0098] Table 6 Comparative Example 3 High Purity Quartz Composition (Unit: ppm)

[0099] element Al B Fe Cu Cr K Mn Zn Na Ti P Ni Mg total SQ1 1.28 0.12 0.96 0.12 0.1 0.13 0.05 0.16 0.22 0.06 0.04 0.01 0.06 3.31

[0100] like Figure 3 As shown, the impurity content of the high-purity quartz prepared in Examples 1 to 3 of the present invention is significantly reduced compared with Comparative Examples 1 to 3, and the purity of the high-purity quartz can be made ≥99.999%, which can be used to prepare quartz crucibles.

[0101] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing high-purity quartz sand from natural quartz sand, characterized in that: The following steps are involved: Step 1, select natural quartz sand with SiO2 content greater than 99% as raw material, use a sieve to control the particle size to less than 200 μm, and wash and dry after screening; Step 2, grinding the quartz sand with a jet mill and then sieving; wherein the mesh size of the sieve is 125000 mesh to 12500 mesh, and the grinding time is 1 to 6 hours; Step 3, putting the screened quartz sand into a reactor, and adding alkaline solution to fully stir the reaction; Step 4, filtering the solution in step 3 to remove precipitated impurities, and removing alkali metal ions through a strong acid cation exchange column, wherein the solution flow rate is 60-180 L / min; Step 5, placing the sol obtained in step 4 into a reaction kettle, starting stirring, allowing to stand for aging after stirring, washing with deionized water for multiple times after aging, and drying after washing; Step 6, using a crusher to crush the dried gel, using a screen to control the quartz sand particle size range to 100-600 μm, and then putting the quartz sand into a high-temperature furnace for calcination and crystallization, the calcination temperature is 1000-1300° C., and the calcination time is 12-36 hours.

2. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1, characterized in that: In step 1, the cleaning includes: first, using deionized water with a pH of 6.8-7.2 to wash away dust and impurities on the surface of the quartz sand, then using a 0.1 mol / L hydrochloric acid solution for pickling, and then washing again with deionized water, and finally using a vacuum drying oven for drying, with the pressure set to -0.1 MPa, the temperature set to 40-60°C, and the drying time being 4-8 hours.

3. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1, characterized in that: In step 2, the jet mill uses a double-jet jet mill with a working pressure of 0.3~0.8MPa and a feed rate of 2~8kg / h; the classifying wheel speed is 1500~3200r / min; the feeder frequency is 25~45Hz; the induced draft fan frequency is 30~45Hz, and the gas flow rate is 200~300m / s; argon, nitrogen or helium is used as the material carrier gas.

4. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1 or 3, characterized in that: In step 2, the quartz sand particle size is divided into larger than 1 μm, 1-0.5 μm, 0.5-0.2 μm, and smaller than 0.2 μm through a sieve.

5. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1, characterized in that: In step 3, the alkaline solution includes one of sodium hydroxide and potassium hydroxide or a mixture thereof, the concentration is 1.2-4.5 mol / L, the reaction temperature is 60-220° C., the reaction time is 4-10 h, and the alkaline solution and the impurity elements in the quartz sand generate silicon slag precipitate.

6. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1, characterized in that: In step 4, the strong acid cation exchange resin is 732 type, the temperature is controlled at 8-15°C, and the pH is 2-3.

7. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1, characterized in that: In step 5, the stirring temperature is 40-120° C., the stirring speed is 80-350 r / min, and the stirring time is 2-15 h; the standing temperature is 60-100° C., and the standing time is 0.5-3 h; the aging temperature is 70-140° C., and the aging time is 3-18 h; the drying temperature is 120-260° C., and the drying time is 18-36 h; all are carried out under the protection of an inert atmosphere.

8. The method for preparing high-purity quartz sand from natural quartz sand according to claim 7, characterized in that: The inert protective gas is nitrogen, helium or argon, the gas purity is ≥99.99%, and the gas flow rate is 200~500mL / min.

9. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1 or 7, characterized in that: In step 5, the inner surface of the reactor is a phenolic coating or a high temperature and corrosion resistant coating with a thickness greater than 15 μm.

10. The method for preparing high-purity quartz sand from natural quartz sand according to claim 1, characterized in that: In step 6, the crusher is a double-toothed roller crusher, the roller shaft is made of high-purity quartz with a purity of ≥99.99%, and the rotation speed is 10~120r / min; the high-temperature furnace is a microwave rotary furnace with a power of 120~200kW and a rotation speed of 0.5~2r / min.

Citation Information

Patent Citations

  • Natural powder quartz purification method, high-purity powder quartz and quartz product

    CN109019609A

  • Hydrothermal synthesis method of high-purity quartz

    CN115744920A

  • Process for purifying and processing 4N-grade high-purity fine-grained quartz sand from natural powdered quartz

    CN117483092A